INTUITION IN AUDITOR'S PROFESSIONAL SKEPTICISM - José Antonio Gouvêa Galhardo (Revista da CGU, 2023)
This article discusses the use of intuition by auditors, exploring its relevance for fraud detection. Auditors are expected to exhibit professional skepticism, which includes a questioning mindset and critical evaluation of audit evidence, but there have been concerns about insufficient use in the practice. While intuition is considered a dangerous trait for auditors due to the risk of biased decisions, it is an essential driver of practice, particularly for risk decisions. Despite the initiatives of professional associations of accountants and auditors, governmental regulators, and international standardization organizations to enhance knowledge about auditors' professional skepticism, there is still a lack of practical guidance on the appropriate use and how to document it. Therefore, the research question is how intuition can be used in the audit process to enhance fraud detection. To address this question, the article provides a literature review of normative, practitioner, and academic production on the use of intuition by auditors as a cognitive approach. The article concludes that the academic literature is scarce, and the normative resistance to the concept by standard-setting organizations may be the cause. The tension between the necessity of sufficient and proper documentation and the exercise of professional skepticism creates a paradox for auditors. Practitioners' commissioned research on auditors' skepticism is essential to bridge the academic literature on intuition and the rule-making by professional and standard-setting organizations. The article proposes a research agenda for the categories: Incentives, Time, Mindset/Prompts, Environmental and Contextual Factors, Competence, and Traits, suggesting alternative research methods such as case studies of corruption and financial scandals. This contribution is essential for auditors, accounting professionals, regulators, and scholars interested in the audit process and enhancing auditors' professional skepticism.